2019
DOI: 10.21273/hortsci13343-18
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Practices and Challenges for Turfgrass Breeders and Distributors

Abstract: Additional index words. breeding priority, turfgrass seeds, marketingAbstract. An online survey was conducted to investigate the current practices of and challenges for turfgrass breeders and turfgrass seed distributors (or sales staff) in the United States. We found that turfgrass seed breeders rated producers/growers and consumers as more important parties compared with other interested parties. However, variations in ratings were found for breeders/distributors according to different program characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The fine fescues are promoted as alternatives for homeowners who wish to establish more sustainable lawns and several studies have revealed that homeowners are willing to buy and use these low input turfgrass species, despite being more expensive, because of their reduced resource input requirements (Hugie et al, 2012;Yue et al, 2021Yue et al, , 2017. While willingness to purchase these grasses is evident, turfgrass breeders and seed distributors rate the volume of seed sales as the most important factor when setting priorities (Yue et al, 2019), so while new markets for low-input turf continue to develop, innovation from private and public breeding programs has not yet translated into expansion of fine fescue acreage. Furthermore, those traits that might be important for seed producers (stand longevity, high yield in a seed production system, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The fine fescues are promoted as alternatives for homeowners who wish to establish more sustainable lawns and several studies have revealed that homeowners are willing to buy and use these low input turfgrass species, despite being more expensive, because of their reduced resource input requirements (Hugie et al, 2012;Yue et al, 2021Yue et al, , 2017. While willingness to purchase these grasses is evident, turfgrass breeders and seed distributors rate the volume of seed sales as the most important factor when setting priorities (Yue et al, 2019), so while new markets for low-input turf continue to develop, innovation from private and public breeding programs has not yet translated into expansion of fine fescue acreage. Furthermore, those traits that might be important for seed producers (stand longevity, high yield in a seed production system, etc.)…”
Section: Introductionmentioning
confidence: 99%